2017
DOI: 10.3892/or.2017.5358
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PTEN/AKT signaling decreases the expression of TUBB3 and TOP2A with subsequent inhibition of cell growth and induction of apoptosis in human breast cancer MCF-7 cells via ATP and caspase-3 signaling pathways

Abstract: The aim of the present study was to evaluate the effects of PTEN/AKT signaling on TUBB3 and TOP2A expression and on the subsequent cell growth of human breast cancer MCF-7 cells. We found that the disease-free survival (DFS) and overall survival (OS) of breast cancer patients with TUBB3‑positive tumors were lower than these rates in the patients with TUBB3-negative tumors. Meanwhile, DFS and OS of breast cancer patients with TOP2A-positive tumors were also lower than these rates in patients with TOP2A-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…This hypothesis is in line with previous literature, since MLT in the liver and brain tissue, even at lower concentrations (100 nM), was able to improve OXPHOS through stimulation of complexes I and IV and protection of these enzymes against oxidative damage, which was closely related to increase in ATP production [7]. In this context, the increase in ATP levels may suppress the AKT pathway [53] and decrease survival, as observed here and reported in breast cancer cells after administration of extracellular ATP to the medium [54]. Therefore, this hormone decreased cell proliferation probably due to the decrease in ROS production that affected pathways of mitosis stimulation and cell survivor.…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis is in line with previous literature, since MLT in the liver and brain tissue, even at lower concentrations (100 nM), was able to improve OXPHOS through stimulation of complexes I and IV and protection of these enzymes against oxidative damage, which was closely related to increase in ATP production [7]. In this context, the increase in ATP levels may suppress the AKT pathway [53] and decrease survival, as observed here and reported in breast cancer cells after administration of extracellular ATP to the medium [54]. Therefore, this hormone decreased cell proliferation probably due to the decrease in ROS production that affected pathways of mitosis stimulation and cell survivor.…”
Section: Discussionsupporting
confidence: 90%
“…Although in this study, we showed that TUBB3 promoted cell growth and invasion in ccRCC, we could not clarify the mechanism by which TUBB3 enhanced cell growth and invasion. Several papers have shown that TUBB3 is involved in cell growth through the interaction of TUBB3 with PTEN [31][32][33]. Previously, we showed that a reciprocal interaction between TUBB3 and PTEN existed in prostate cancer [34].…”
Section: Discussionmentioning
confidence: 93%
“…Topoisomerase 2A (TOP2A), a member of the DNA topoisomerases, is an enzyme that controls DNA superhelicity and unlinks double-stranded DNA segments during processes such as replication and transcription 17,18 . Many studies have shown that TOP2A plays a crucial role in the tumorigenesis and progression of a variety of malignancies, such as adrenocortical carcinoma 19 , bladder cancer 20 , prostate cancer 21 , liver cancer 22 , and breast cancer 18,23 . Analysis of the molecular data in the CGGA database con rmed that there was a strong correlation between TOP2A and NUSAP1 expression in gliomas samples.…”
Section: Discussionmentioning
confidence: 99%